Effect of grinding methods and packaging materials on fenugreek and black pepper powder quality and quantity under normal storage conditions - Meghwal, Murlidhar; Goswami, T K (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: The effect of different grinding methods and packaging materials on qualities of fenugreek and black pepper powders was evaluated. Various parameters and their evaluation methods are as follows: change in colour determined using Chroma meter calorimeter, aroma and odour measured by sensory evaluation, and change in moisture measured using oven drying method. Packaging materials such as glass jar, steel jar, plastic jar, aluminum bag and poly bags were used for keeping ambient and cryogenically ground fenugreek and black pepper powders. Packed powders were stored in dry and cool places under ambient condition. Sensory evaluation revealed quality reduction in terms of colour, odour, flavour, aroma and acceptability for fenugreek and black pepper powder stored for a long term (6 months). However, glass jar and steel jar were found to be better containers for storing powders for longer storage period than other options. For practical applications, the present investigation on the deterioration behaviour of fenugreek and black pepper powder contributes to the design of a suitable grinder out of ball, hammer, rotor, and pin mill for spice grinding. The study also helps select a suitable packaging material or container to store spice powders. A method to assess the quality of stored powder and its deterioration with the storage time is provided. Keywords: quality deterioration, behaviour; aroma; cryogenic; ambient; packaging DOI: 10.3965/j.ijabe.20140704.012 Citation: Meghwal M, Goswami T K. Effect of different grinding methods and packaging materials on fenugreek and black pepper powder quality and quantity under normal storage conditions. Int J Agric & Biol Eng, 2014; 7(4): 106-113.